(3aQGjO ahGjO bdGFO GdeQLGf hehGQO efShN GdbQBfs - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s
(3ChdgG (B:s
(3QHfG BJfG ef dOfc QMeg hgjF dfG ef CeQfG QTOkG hHYO abO ESJNQJ Gddg JYGdi ai LeY Led ef GdaQGFO GdMSGf hJdNjU ahGjO LeI YXjeI GdTCf ef cJGHi GdehShe HbdGFO GdeQLGf ai GdfGSN hGdefShN ef GdbQBf s
(3BNQgG (B:s
(3hCWhd Bjg CjI GdOjf hCbUQ BjI Ke fXQ hCWhd cdeI djSJNdafge hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs